Broadband Multi-Shaped Metasurface Circularly Polarized Antenna With Suppressed Non-CP Radiation Modes - Nathapat Supreeyatitikul; Titipong Lertwiriyaprapa; Nonchanutt Chudpooti; Monai Krairiksh; Chuwong Phongcharoenpanich (IEEE Open Journal of Antennas and Propagation, 2023)
In this research, a multi-shaped metasurface broadband circularly polarized (CP) patch antenna with parasitic elements is proposed for 5G new radio (NR) applications. The proposed metasurface CP patch antenna comprises triple-layered substrates without air gap. The upper layer sits with multi-shaped metasurface elements and parasitic patches. The middle layer consists of an L-shaped slot functioning as the ground plane, and the lower layer contains a microstrip and a fan-shaped stub functioning as the feed line. The proposed metasurface CP patch antenna with parasitic elements is evaluated using characteristic mode analysis (CMA). The CMA results indicate that the modal significance of Modes 1 and 2 of the multi-shaped metasurface CP antenna are orthogonal, giving rise to circular polarization. The non-CP radiation of Modes 3 and 4 are suppressed by using the multi-shaped metasurface elements and parasitic patches. The measured impedance bandwidth and axial ratio bandwidth are 42.85% (3.4 -4.9 GHz) and 38% (3.27 -4.6 GHz), achieving the maximum gain of 7.23 dBic at 3.7 GHz. The experiments demonstrate that the multi-shaped metasurface CP patch antenna with parasitic elements is suitable for 5G NR wireless applications. The novelty of this study is attributed to its utilization of multi-shaped metasurface elements and parasitic patches, which effectively suppress non-circularly polarized radiation modes.
Keywords: Antenna Design and Analysis; Advanced Antenna and Metasurface Technologies; Energy Harvesting in Wireless Networks